Safety and efficacy of Calsporin(®) (Bacillus subtilis DSM 15544) for all poultry species - Bampidis, Vasileios (EFSA J, 2019)
The additive Calsporin(®) is a preparation of viable spores of Bacillus subtilis DSM 15544, at a minimum declared concentration of 1 × 10(10) colony forming units (CFU)/g additive. The additive is authorised as a zootechnical additive (functional group: gut flora stabiliser) for use in chickens for fattening, weaned piglets, chickens reared for laying, turkeys, minor avian species and other ornamental and game birds, laying hens and ornamental fish, dogs, in sows and in suckling piglets. This opinion concerns a request for a modification of the terms of the authorisation, reducing the minimum content in complete feed for chickens for fattening from the authorised concentration of 5 × 10(8) CFU/kg feed to a concentration of 3 × 10(8) CFU/kg feed and for an authorisation for the use of the additive for all poultry species. The active agent fulfils the requirements of the qualified presumption of safety (QPS) approach to the assessment of safety and no concerns are expected from other components of the additive. Consequently, Calsporin(®) is considered safe for the target animals, the consumers and for the environment. The additive is not a dermal/eye irritant or a skin sensitiser but should be considered a potential respiratory sensitiser. The additive has the potential to be efficacious as a zootechnical additive in feedingstuffs for chickens for fattening at the level of 3 × 10(8) CFU/kg complete feed. Considering that efficacy at the same level has been shown in laying hens and turkeys, this conclusion is extrapolated to all poultry species and categories.